A neural-based MAC protocol for distributed wireless LANs - Nicopolitidis, P.; Papadimitriou, G.I.; Pomportis, A.S.; Oboidat, M.S. (SMC'03 Conference Proceedings. 2003 IEEE International Conference on Systems, Man and Cybernetics. Conference Theme - System Security and Assurance (Cat. No.03CH37483), 2003)
A self-adaptive neural-based MAC protocol for distributed wireless LANs, capable of operating efficiently under bursty traffic conditions, is introduced. According to the proposed protocol, the mobile station that is granted permission to transmit is selected by means of a neural-based algorithm. The neural-based algorithm takes into account the network feedback information in order to update the choice probability of each mobile station. The proposed protocol is compared via simulation to TDMA and is shown to exhibit superior performance under bursty traffic conditions even when the network feedback is noisy.